NGHIÊN CỨU CỐ ĐỊNH VI SINH VẬT BẰNG CANXI ALGINAT ỨNG DỤNG TRONG CẢM BIẾN SINH HỌC XÁC ĐỊNH NHANH NHU CẦU OXY SINH HÓA - Lê, Thị Bảo Ngọc; Huỳnh, Thị Kim Trang; Dương, Huỳnh Thanh Linh; Nguyễn, Thị Thùy Vân; Hoàng, Tiến Cường; Nguyễn, Phúc Hoàng Duy; Phạm, Thị Thùy Phương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
IMMOBILIZATION OF MICROORGANISMS USING CANXI ALGINAT FOR RAPID ESTIMATION OF BIO-CHEMICAL OXIDATION DEMAND BY BIOSENSOR Immobilized microorganisms have been shown to have outstanding advantages over the free ones, especially in the field of wastewater treatment. Natural gel materials such as alginat allow substrates to diffuse well across the membrane, thereby improving the efficiency of immobilized microbial activity. These supports, however, appeared to be swollen or even soluble during treatment. In this study, the factors affecting the stability of canxi alginat beads and the activity of immobilized microorganisms in the BOD biosensor were investigated. By changing the needle size and distance, the particle size of alginat beads can be adjusted. The results show that the smaller the particle size, the higher metabolic activity of immobilized microorganisms; however, very small alginat beads whose diameter is less than 2.3 mm are not stable. Immersion in CaCl2 solution of 0.4% can maintain the stable activity of immobilized microorganisms in alginat beads up to more than 66 days. By using the prepared alginat d beads and GGA standard solutions, the developed biosensor can accurately predict the BOD5 value of wastewater from paper mills.